Dimensiones de la comunicación familiar en los adolescentes de 4° año de secundaria de la I.E. N° 80892 “Los Pinos” Trujillo – 2017. - Rosales Llacza, Sandra Elizabeth (2018)
The present investigation is descriptive, of quantitative approach, descriptive level and non experimental experimental design of cross section, whose objective is to know the dimensions of the communication of the adolescents of the 4th year of secondary education of the I.E. N ° 80892 "LOS PINOS" of Trujillo in the year 2017. The sample consists of 73 students, the RFCP scale was used. This investigation presents five chapters. Chapter I presents the theoretical framework, background, theoretical bases and conceptual framework, the approach to the problem, the hypothesis and objectives of the research. In chapter II the methodology is presented, the methods, techniques, instruments and sample universe are presented, in chapter III, corresponds to the presentation of results, through statistical tables and graphs; Chapter IV, contains the processing, analysis, and discussion of the results; Finally, the conclusions and recommendations and the presentation of all the annexes are presented. The results obtained allow us to lay the foundations for the formulation of an Intervention Program, evidencing the transcendental importance of parent-adolescent communication, aimed at promoting clear and positive communication among them.